An evaluation of some measures of core inflation for the euro area - Juan Luis Vega; Mark A. Wynne (European Central Bank (ECB), 2001)
We examine two measures of core inflation which have been proposed in recent years: the limited-influence estimators of core inflation pioneered by Bryan and Cecchetti (1994); and the Edgeworth or variance-weighted price index discussed by Diewert (1995). We compare these measures with traditional 'Ex. Food & Energy'-type measures and evaluate them on the basis of two criteria: their ability to track movements in trend inflation; and their ability to predict future headline inflation. We do find evidence that traditional 'Ex. Food & Energy'-type measure of core inflation may be dominated by alternative measures and conclude that trimmed-mean measures of core inflation may be a useful input to the monetary policy process. These conclusions, nonetheless, are necessarily tentative and subject to strong caveats due to the short span of data on which inference can be drawn
Keywords: E31; 330; core inflation; euro area; HICP